ADDITIONAL VALID RECORD OF MARBLED HAWKFISH , Cirrhites pinnulatus (BLOCH & SCHNEIDER, 1801) (PERCIFORMES: CIRRHITIDAE) FROM NORTH SULAWESI - Teguh Peristiwady (Indonesian Fisheries Research Journal, 2008)
The specimen of marbled hawkflsh, Cirrhites pinnulatus (Bloch & Schneider, 1801) (136.30 mm SL) was collected by spear gun from reef flat of Kema, Bitung, North Sulawesi. Some valid record of this species were found and recorded from lndo-Pacific and Indian Ocean.